Iodine Status Has No Impact on Thyroid Function in Early Healthy Pregnancy. (28th November 2012) - Brucker-Davis, F.; Ferrari, P.; Gal, J.; Berthier, F.; Fenichel, P.; Hieronimus, S.
Abstract : Aim . To assess the impact of iodine status in early pregnancy on thyroid function. Methods . Women >18 years old seen at their first prenatal consult before 12 weeks of amenorrhea and without personal thyroid history were proposed thyroid screening and were eligible if they had strictly normal thyroid tests (fT4 > 10th percentile, TSH < 2.5 mUI/L, negative anti-TPO antibodies). Evaluation included thyroid ultrasound, extensive thyroid tests, and ioduria (UIE). Results . 110 women (27.5 y, 8 weeks of amenorrhea, smoking status: 28% current smokers) were enrolled. Results are expressed as medians. UIE was 116  μ g/L. 66.3% of women had iodine deficiency (ID) defined as UIE < 150. FT4 was 14.35 pmol/L; TSH 1.18 mUI/L; fT3 5 pmol/L; thyroglobulin 17.4 ng/mL; rT3 0.27 ng/mL; thyroid volume: 9.4 ml. UIE did not correlate with any thyroid tests, but correlated negatively with thyroid volume. UIE and all thyroid tests, except fT3, correlated strongly with β hCG. Smoking correlated with higher thyroid volume and thyroglobulin and with lower rT3. Conclusions . In pregnant women selected for normal thyroid function, mild ID is present in 66% during the 1st trimester. The absence of correlation between UIE and thyroid tests at that stage contrasts with the impact of β hCG and, to a lesser degree, maternal smoking.